Evacuation route optimization under real-time toxic gas dispersion through CFD simulation and Dijkstra algorithm. (May 2022) - Wang, Jiyun; Yu, Xiaoyang; Zong, Ruowen; Lu, Shouxiang
Abstract: Evacuation route optimization plays an important role in safe evacuation for toxic leakage accidents. We propose an approach for route optimization under real-time toxic gas dispersion by combining computational fluid dynamics (CFD) code and the Dijkstra algorithm. CFD code is used to simulate the toxic gas dispersion to predict the spatial-temporal distribution of concentrations, which is related to the calculation of the inhaled dose. Taking the dose as the weights of arcs, the concentrations predicted by CFD are embedded into the modified Dijkstra algorithm to calculate the optimal route with minimal total inhaled dose. The results show that the time before evacuation affects the evacuation route optimization, and the death probability exhibits an "S"-shaped growth as time increases. The optimal route may vary with wind direction dominating the direction of toxic gas dispersion because of the change of weights of arcs. Workers wearing protective equipment are allowed to pass through areas with high-concentration toxic gas, and the length of the optimal evacuation route decreases with the level of safety protection. The proposed methodology with appropriate modification is suitable for evacuation route optimization in fires. Highlights: An approach for route optimization under toxic gas dispersion is proposed. The modified algorithm combining CFD results and Dijkstra algorithm is presented. The real-time toxic gas dispersion is performed by CFD simulation. Effect of pre-evacuation time on the route optimization is investigated. Effect of safety protection on the route optimization is quantified.